An Ohmic contact behavior of flexible thick film carbon-based electrode with TiO2 layer at different operating temperature - Abu Bakar, Azlinda; Hamidon, Mohd Nizar; Yaacob, Mohd Hanif; Paiman, Suriati; Jaafar, Haslina; Shafiee, Farah Nabilah; Hasan, Intan Helina (International Scientific Organization, 2023)
An electrical property of a carbon-based referring to graphite and multiwall carbon nanotube (MWCNT) as conductive paste with titanium dioxide TiO2 were presented in this research work. Screen printing technique has been selected to deposit graphite and MWCNT thick film respectively on kapton film substrate. Each conductive paste was fired at 1500C before printing TiO2 paste printing on top as metal-oxide layer followed by another firing at 3500C. The electrical properties measurement was performed using Current-Voltage (I-V) characteristics measurement from -10 V to +10 V, at various temperatures from 28, 50, 100, 150, 200, to 2500C. The I-V results have shown linear and symmetric I-V relationship indicating good Ohmic contact between carbon based and TiO2 thick film. The resistance value of graphite has a low value compared to MWCNT at room temperature measurement. Meanwhile the resistance values for Graphite/TiO2 and MWCNT/TiO2 showed a decreasing trend again increase the temperature operations associated with slower electron mobility effect of TiO2.